Comparison of Outcomes of Open versus Laparoscopic Living Donor Nephrectomy in Nepal - Sigdel, Prem R; Gnyawali, Diwas; Rai, Bipendra DK; Dhital, Pawan; Parajuli, Purushottam; Chudal, Sampanna; Dhakal, Niraj; Pradhan, Manish; Poudyal, Sujeet; Poudyal, Sujeet; Chapagain, Suman; Luitel, Bhoj R; et al. (Journal of Institute of Medicine Nepal, 2020)
Introduction Laparoscopic donor nephrectomy is the gold standard for kidney retrieval in live donors. Until recently, donor nephrectomies were performed only by open technique in Nepal. There is no information on the experience and outcomes of laparoscopic donor nephrectomy in Nepal. The study was done to compare the outcomes among donors undergoing open and laparoscopic nephrectomies, and to compare the graft related outcomes between the two groups receiving these kidneys.MethodsIn this retrospective study, 44 kidney donors from March 2019 to October 2019 were analyzed. Donors were divided into 2 groups: open donor nephrectomy (ODN) and laparoscopic donor nephrectomy (LDN). Parameters for analysis included demographic data, warm ischemia time, surgery time and length of hospital stay. Data on early graft function and complications in recipients till 30th post-operative day were compared.ResultsThere were 22 donors each in the ODN and LDN groups. Baseline characteristics of the donors were comparable between two groups. Mean surgery duration (183.55±43.31 minutes vs 117.73±18.75 minutes) and first warm ischemia time (11.22±4.34 minutes vs 2.3±0.8 minutes) was significantly high in LDN. Hemoglobin drop, post-operative complications in donors, creatinine of donors at discharge, mean hospital stay, graft function at one month and complications in recipients were comparable among ODN and LDN. Pain score in 1st post-operative day was comparable between two groups, however, pain was significantly less in second post-operative day in LDN.ConclusionLaparoscopic donor nephrectomy is feasible in Nepal and associated with acceptable morbidity and graft function when compared to ODN.